A Framework for Open World Object Detection - Shaheen, Khadija; Hanif, Muhammad Abdullah; Hasan, Osman; Shafique, Muhammad (Artificial Intelligence Evolution, 2023)
Open World Object Detection (OWOD) is a computer vision task that focuses on real-world scenarios where object detection algorithms need to not only detect known and labeled objects but also handle novel and unknown objects that were not seen during training. This distinguishes OWOD from traditional object detection benchmarks, where the scope is limited to detecting only known object classes. The main challenge in OWOD lies in detecting and classifying unknown objects, which were not part of the training data. In standard object detection, objects not overlapping with labeled objects are automatically classified as background. However, these approaches are not suitable for OWOD, as unknown objects may be wrongly predicted as background due to the lack of specific supervision for distinguishing unknown objects from the background. The paper proposes a novel framework for Open World Object Detection called Open World Object Detection based on Non-Parametric classification (OWOD-NP). This method aims to address the challenges of identifying unknown objects and extending the knowledge base by incrementally introducing new object categories. OWOD-NP incorporates a non-parametric learning approach based on mean prototypes and rejection criteria into a standard detector model. The non-parametric learning model allows the system to detect whether the perceived region contains an unknown object and perform incremental learning in an end-to-end manner. The extensive experiments conducted on the benchmark dataset of Pascal Visual Object Classes (VOC) validate the effectiveness of OWOD-NP. Compared to the standard faster RCNN model, OWOD-NP achieves approximately 14% higher mean Average Precision (mAP) in class incremental scenarios. This improvement showcases the capability of OWOD-NP to handle open-world object detection tasks more efficiently. By combining non-parametric learning with object detection, OWOD-NP provides a promising solution for open-world scenarios, where the environment is dynamic and new objects may appear over time. The ability to detect and classify both known and unknown objects makes OWOD-NP a valuable approach for real-world applications in robotics, autonomous systems, and other computer vision tasks. It allows for continuous adaptation and learning, enabling the system to extend its knowledge and cope with ever-changing environments effectively.